2001
DOI: 10.1161/01.cir.103.21.2631
|View full text |Cite
|
Sign up to set email alerts
|

Left-to-Right Gradient of Atrial Frequencies During Acute Atrial Fibrillation in the Isolated Sheep Heart

Abstract: Background-Recent studies demonstrated spatiotemporal organization in atrial fibrillation (AF). We hypothesized that waves emanating from sources in the left atrium (LA) undergo fragmentation, resulting in left-to-right frequency gradient. Our objective was to characterize impulse propagation across Bachmann's bundle (BB) and the inferoposterior pathway (IPP) during AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
308
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 341 publications
(332 citation statements)
references
References 39 publications
(46 reference statements)
22
308
0
2
Order By: Relevance
“…As persAF is a more complex arrhythmia than pAF, the identification of atrial areas for successful ablation in patients with persAF remains a challenge due to the co-existence of multiple arrhythmogenic mechanisms [4,35]. Previous works have shown that the DF measured from AEGs correlates with the local main activation wave during persAF [9, 14,36].…”
Section: Mechanisms For Persaf Maintenancementioning
confidence: 99%
“…As persAF is a more complex arrhythmia than pAF, the identification of atrial areas for successful ablation in patients with persAF remains a challenge due to the co-existence of multiple arrhythmogenic mechanisms [4,35]. Previous works have shown that the DF measured from AEGs correlates with the local main activation wave during persAF [9, 14,36].…”
Section: Mechanisms For Persaf Maintenancementioning
confidence: 99%
“…28 Similar LA to RA DF 28 gradients were reproduced in a subsequent study by the same group (see Figure 7). 29 Because the frequency of rotational activity was so high, only tissue in close proximity to the rotor could activate in a 1:1 fashion, and at distant sites the wavefronts underwent wavebrake and initiated chaotic and fibrillatory conduction. 29 Lazar et al extended the concept of DF mapping to humans and demonstrated LA to RA DF gradients in patients with paroxysmal AF, with the highest DFs at the junction between the pulmonary veins and the LA.…”
Section: Evidence For Rotors and Other High Frequency Sources As Drivmentioning
confidence: 99%
“…29 Because the frequency of rotational activity was so high, only tissue in close proximity to the rotor could activate in a 1:1 fashion, and at distant sites the wavefronts underwent wavebrake and initiated chaotic and fibrillatory conduction. 29 Lazar et al extended the concept of DF mapping to humans and demonstrated LA to RA DF gradients in patients with paroxysmal AF, with the highest DFs at the junction between the pulmonary veins and the LA. This gradient, however, was not present among patients with persistent AF, again suggesting a different mechanism for sustaining AF of longer duration.…”
Section: Evidence For Rotors and Other High Frequency Sources As Drivmentioning
confidence: 99%
“…Recently, Mansour and colleagues, 9 using optical and electrical mapping techniques, have shown a gradient of frequencies between the left and right atria in the acetylcholine-mediated, pacing-induced model of sustained AF in isolated sheep hearts. In their experiments, the LA demonstrated organized electrical activity with the presence of a dominant frequency (DF), which was consistently higher than those in the recordings from the right atrium (RA).…”
mentioning
confidence: 99%